2021
DOI: 10.3390/nano11092417
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Preferred Orientation of Silver-Plating via X-ray Diffraction Profile

Abstract: Determining the preferred orientation of plating film is of practical importance. In this work, the Rietveld method and quantitative texture analysis (RM+QTA) are used to analyze the preferred orientation of plating silver film with XRD profile, whose <311> axial texture can be completely described by a set of exponential harmonics index, extracted from a single XRD profile, C41,1(0.609), C61,1(0.278), C81,1(−0.970). The constructed pole figures with the index of the exponential harmonic are following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…XRD analysis of the films before and after annealing reveals several diffraction peaks at 31.8°, 34.4°, 36.3°, and 56.7°, corresponding to the (100), (002), (101), and (110) crystallographic planes in ZnO (see figure 1), which exhibit a wurtzite hexagonal crystal structure consistent with previous reports [29,30]. All the films exhibit a polycrystalline structure with a dominant peak at 34.42°, indicating preferential grain orientation along the c-axis [31]. This preferential orientation is preserved across all annealing temperatures.…”
Section: Structural Propertiessupporting
confidence: 85%
“…XRD analysis of the films before and after annealing reveals several diffraction peaks at 31.8°, 34.4°, 36.3°, and 56.7°, corresponding to the (100), (002), (101), and (110) crystallographic planes in ZnO (see figure 1), which exhibit a wurtzite hexagonal crystal structure consistent with previous reports [29,30]. All the films exhibit a polycrystalline structure with a dominant peak at 34.42°, indicating preferential grain orientation along the c-axis [31]. This preferential orientation is preserved across all annealing temperatures.…”
Section: Structural Propertiessupporting
confidence: 85%
“…It has been argued that Ag may deposit preferably in ( 111) and (200) orientation, since these orientations show the lowest surface energy. However, the (311) orientation is theoretically even more preferred when regarding the combination of surface and strain energy minimization 32,33 . In our study, we found that the (111) orientation is preferred for the Ag deposition under DHBT conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the intensity calculations, the Lorentz factor is joined with the polarization factor and further, the variation of the Lorentz's factor with the Bragg angle (θ) is shown. [55][56][57][58] The general effect of the Lorentz factor is to diminish the intensity of the reflections at intermediate angles contrasted with those in the forward or backward directions. Lorentz factor and Lorentz Polarization factor are determined from Equations ( 17) and ( 18) separately and arranged in Table 6.…”
Section: Xrd Dislocation Density and Micro Strainmentioning
confidence: 99%